A systems approach to flood vulnerability. Issue 3 (2nd July 2016) - Beevers, Lindsay; Walker, Guy; Strathie, Ailsa
ABSTRACT: Flood vulnerability is an internationally important problem with no easy solution. In this paper it is argued that vulnerability is an emergent output of interacting human and engineering components, and that to make further progress on usefully deploying the concept, a systems approach is needed. The existing state of the art in Flood Vulnerability Indices is blended with a constraints-based systems engineering approach called an Abstraction Hierarchy. Four existing towns were modelled using this approach, and the impact of a 1–200 year flood was assessed, by focusing on the key interactions within the model. As the flood waters progressively removed physical objects in the system, higher-level processes and functions became systematically degraded. Via this process, the modelled towns were revealed to be low on exposure, high on susceptibility, but low on resilience. This is one of eight vulnerability types possible. Different flood risk solutions can be associated with different vulnerability types. Comparing these outputs to real-life policy and practice reveals some interesting areas of mismatch.